LA PAZ Y EL FUTURO DE CENTROAMÉRICA PROPUESTAS DE NEGOCIACIÓN Y ACTORES INTERNACIONALES - Solís Rivera, Luis Guillermo (2015)
As a way to face the crisis that has affectedthe area of Central America for nearly a decade,the five presidents of the isthmus metin Guatemala City on August 7, 1983 for theestablishment of peace in Central America.Therefore, this article will analyze the characteristicsof the agreed process in Guatemalaand Central America’s relations with the internationalcommunity.